Grupos Balint com internos de medicina de uma universidade pública do Nordeste: sentimentos, crenças e atitudes - Nogueira, Trícia Feitosa (2016)
The Medical School of the Federal University of Ceará Sobral started on 02.04.2001, whose political-pedagogical project of the course of Fortaleza of Medicine (1995) indicated the completion of Balint groups seminars to discuss situations during boarding. Objective. To evaluate the use of Balint Groups on the professionalism of Internal Medicine. Methodology. Descriptive study performed from 20/02 to 31/07/2012, with clinical-qualitative approach to content collected in 37 sessions of Balint Group (GB) with 17 students from boarding school, called Group 1 - Pilot (9 students) and Group 2 - Balint group search (8 students). The GB took place in an appropriate environment of a hospital in the State of Ceará and were recorded in audio, whose research scenarios are the reports of the situations, called cases trigger. The group process occurred in three phases: planning and evaluation activities. ethical procedures relevant to the research were observed and the project approved by Nº. 344/11 of 16/02/2012 Protocol on validity of Resolution Nº. 196/96. The material was organized based on content analysis by the criterion of relevance. Results. There were 28 trigger cases in the seven contexts: Internal Medicine, Surgery, Obstetrics and Gynecology, Pediatrics and Community Health (Emergency Family Health Strategy and Mental Health) that the 25 Feelings category set of subcategories only three, there are positive reports: happiness, feel fulfilled and useful. The other denote negative feelings: guilt, anger, disappointment, sadness, fear, worry, anger, hopelessness and difficulty accepting the death. Within the category Beliefs are 24 subcategories. Although two of the eight internal find themselves saviors, others recognize the limit, but indicated that the health system does not help to bond with patients, especially in Surgery, Gynecology and Family Health Strategy. The whole category Attitudes are 25 subcategories and Communication was the most cited among them, followed by the Decision Making, the interdisciplinarity and the Link to the effective inner-patient relationship and internal multidisciplinary team. After the description of the narratives with interpretation was made, it contains the evaluation of internal in the six meetings held. Conclusions. The findings supported the international literature indicate problematic attitudes whose heroic roles are in discussions about medical identity, ethical dilemmas and the history centered on the patient, the GB themes performed by undergraduate students.